2004
DOI: 10.1207/s15430154jce1901_08
|View full text |Cite
|
Sign up to set email alerts
|

Disparities between Public Health Educational Materials and the Scientific Evidence that Smokeless Tobacco Use Causes Cancer

Abstract: Communication of the health risks of using ST must be done accurately and should be data based. Broadening the message to include additional diseases for which the evidence is inadequate could cause the message about true risks, as well as the messenger, to be discounted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…However, respondents perceived ST as high risk for all health domains, and over 80% perceived it to be the same or higher risk than smoking for oral cancer. These perceptions are in stark contrast to the scientific evidence [5,6] and expert assessments [8][9][10]20]. At least half of the respondents in this study considered ST and cigarettes to be of equal risk for general health, all cancer and oral cancer, which is consistent with other surveys [21][22][23].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, respondents perceived ST as high risk for all health domains, and over 80% perceived it to be the same or higher risk than smoking for oral cancer. These perceptions are in stark contrast to the scientific evidence [5,6] and expert assessments [8][9][10]20]. At least half of the respondents in this study considered ST and cigarettes to be of equal risk for general health, all cancer and oral cancer, which is consistent with other surveys [21][22][23].…”
Section: Discussionsupporting
confidence: 69%
“…Another systematic review of over 48 medical brochures from some of the same organisations (e.g. NCI and ACS) found that the risk of oral cavity cancer and of other conditions associated with ST use was frequently overemphasised, 'reaching beyond the scientific data' [20]. This misinformation may have played a role in the risk perceptions of ST that we have observed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, they did make many literally true misleading claims, including saying "not a safe alternative" [30-32], and lumping together attributable risk from ST for oral cancer with the (many times greater) attributable risk from cigarettes [32,33]. A particularly misleading conjunction is, "Smoking tobacco, using smokeless tobacco, and being regularly exposed to environmental tobacco smoke are responsible for one-third of all cancer deaths in the United States each year" [34]. Even the worst-case scenario for claims about the risk from ST would make it responsible for in the order of 1/1000 of this attributable risk.…”
Section: Resultsmentioning
confidence: 99%
“…In all of these studies ST use was not associated with a significant increase in mouth cancer risk. In 2004 a group of epidemiologists concluded that the evidence linking ST use and oral cancer was "not decisive" [94]. These investigators commented that many claims in the media "overemphasize the risk of oral cavity cancer [from ST use], reaching beyond the scientific data.…”
Section: Smokeless Tobacco Usementioning
confidence: 99%